Effect of desert sand on the uniaxial compressive properties of mortar after elevated temperature - Zhang, Qian; Liu, Qiang; Liu, Haifeng; Che, Jialing; Chen, Xiaolong; Doh, Shu Ing (Elsevier Ltd., 2021)
In China, medium sand is widely used for engineering applications. However, over quarrying of medium sand to meet the demand for urbanization has led to the environmental issue. The arid area of Northwest China, which has high concentration of desert could provide sufficient supply of desert sand for engineering applications. In this paper, desert sand was used to replace medium sand to produce desert sand mortar (DSM). The uniaxial compression test was performed on the DSM undergoing elevated temperature treatment, and the stress-strain curves of the DSM after different temperatures were obtained. The effects of temperature and desert sand replacement rate (DSR) on the peak stress, peak strain, elastic modulus, Poisson's ratio, and mass loss rate of DSM was analysed. The test results showed that with the increase of DSR, the peak stress and elastic modulus of DSM first increased and then decreased. As the temperature increased, the Poisson's ratio of the DSM decreased first and then increased. Based on regression analysis, the relationships between peak stress, peak strain, elastic modulus, Poisson's ratio of DSM, temperature, and DSR were obtained. At the same time, a one-parameter compression constitutive equation of DSM after the elevated temperature was established. Since the equation has only one parameter, the calculation process was greatly simplified based on ensuring the calculation results. The model was in high agreement with the test results. This equation can provide a reference for further studies in the field of mechanical properties of DSM and desert sand concrete (DSC) after elevated temperatures.